Growth and venture capital investment potential for university spin-offs in Hungary - Becsky-Nagy, Patrícia (Applied Studies in Agribusiness and Commerce, 2013)
Venture backed spin-offs represent a low proportion of companies, even of innovative companies. The research question was, whether these companies have an important role in innovation and economic growth. I present the most important indicators of innovation in connection with entrepreneurship, the measures of start-ups, mainly the high-tech ones. I describe the position of venture capital industry nowadays, detailing the classical venture capital investments, targeting high-growth potential small firms, even university spin-offs. The study presents the results of a survey made as a counterpart of an academic research team, examining spin-offs, entrepreneurs and technology transfer in the most important Hungarian universities. I found that the most important obstacles of venture capital investments in high-tech spin-offs are the information gap between demand and supply side, the lack of entrepreneurs’ willingness to give up freedom in decision making, despite of low managerial skills. The low quality of financial environment is also an obstacle of the segment. JEL Codes: G24, M13